Gastric Bezoar - A Rare Presentation in Infant (Journal of Paediatric Surgeons of Bangladesh, 2016)
Gastric bezoar in neonate is a rare presentation. Because of rarity of phytobezoar and lactobezoar are not considered as the differential diagnosis of a lump and vomiting commonly. A 7 month female presented with left upper abdominal undifferentiated hard mobile lump and post prandial occasional vomiting. Diagnosis was non-conclusive with USG, contrast medium study of stomach and duodenum and contrast enhanced CT scan. After laparotomy and gastrostomy mass was removed and diagnosed as phytolactobezoar on macroscopic appearance.J. Paediatr. Surg. Bangladesh 6(1): 24-27, 2015 (Jan)